Polarizing plate and method for manufacturing the same, and image display device

By forming a layer containing urea-based compound on the surface of the polyvinyl alcohol-based resin polarization element and combining it with a transparent protective film, the problem of lowering the transmittance of the polarizing plate under a high temperature environment is solved, and the high-temperature durability of the image display device is realized and Improved display performance.

CN113811797BActive Publication Date: 2025-02-14SUMITOMO CHEM CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202080034704.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-15
Filing Date
2020-05-08
Publication Date
2025-02-14
Estimated Expiration
2040-05-08

AI Technical Summary

Technical Problem

Under high temperature environment, the transmittance of the polarizing plate in the image display device used for interlayer filling is significantly reduced, affecting the display performance.

Method used

A layer containing a urea compound is formed on at least one surface of the polyvinyl alcohol-based resin polarization element, and a layer containing an adhesive layer and a transparent protective film are combined to prevent a decrease in the transmittance in a high temperature environment.

Benefits of technology

It effectively suppresses the reduction of the transmittance of the polarizing plate under high temperature environment, and improves the durability and display performance of the image display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The object of this invention is to provide a polarizing plate that, when used in an image display device with interlayer filling, exhibits minimal reduction in transmittance under high-temperature conditions and excellent durability, and to provide a method for manufacturing the polarizing plate. Furthermore, another object of this invention is to provide a durable image display device with improved display characteristics under high-temperature conditions. This invention provides a polarizing plate characterized by comprising a polyvinyl alcohol-based resin polarizing element formed by adsorbing and orienting iodine, a layer formed on at least one surface of the polarizing element containing a urea-based compound selected from urea, urea derivatives, thiourea, and thiourea derivatives, and a transparent protective film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing plate and a method for producing the same. In addition, the present invention relates to an image display device in which one surface of the polarizing plate is bonded to an image display unit and the other surface is bonded to a transparent member such as a touch panel or a front panel. Background Art

[0002] Liquid crystal display devices (LCD) are not only used in liquid crystal televisions, but are also widely used in personal computers, mobile devices such as mobile phones, and in-vehicle applications such as navigation systems. Generally, a liquid crystal display device has a liquid crystal panel member with polarizing plates attached to both sides of a liquid crystal cell with an adhesive, and displays are performed by controlling light from a backlight member using the liquid crystal panel member.

[0003] In recent years, organic EL display devices have also begun to be widely used in televisions, mobile devices such as mobile phones, and in-vehicle applications such as navigation devices, just like liquid crystal display devices.

[0004] In an organic EL display device, in order to prevent external light from being reflected by the metal electrode (cathode) and observed as a mirror surface, a circular polarizing plate (a laminate including a polarizing element and a λ / 4 plate, sometimes simply referred to as a polarizing plate) is sometimes arranged on the visible side surface of the image display panel.

[0005] As mentioned above, polarizing plates are increasingly being installed in vehicles as components of liquid crystal display devices and organic EL display devices. Polarizing plates used in vehicle-mounted image display devices are more often exposed to high-temperature environments than those used in other mobile devices such as televisions and mobile phones, and are required to have less change in characteristics under high temperatures (high-temperature durability).

[0006] On the other hand, for the purpose of preventing damage to the image display panel caused by impact from the external surface, the configuration of providing a front panel (also called a "window layer" or the like) such as a transparent resin plate or a glass plate on the visible side of the image display panel relative to the polarizing plate is increasing. In addition, in a display device having a touch panel, a configuration of providing a touch panel on the visible side of the image display panel relative to the polarizing plate and providing a front panel on the visible side relative to the touch panel is widely adopted.

[0007] In this structure, if there is an air layer between the image display panel and transparent components such as the front panel and the touch panel, reflected glare of external light caused by the reflection of light is generated at the interface of the air layer, and the visibility of the picture tends to decrease. Therefore, the use of a structure in which the space between the polarizing plate arranged on the visible side surface of the image display panel and the front transparent component is filled with a material having a refractive index close to these materials (hereinafter sometimes referred to as an "interlayer filling structure") is expanding. As an interlayer filling material, an adhesive or a UV curing adhesive is used for the purpose of suppressing the reduction in visibility caused by reflection at the interface and bonding and fixing the components (for example, refer to Patent Document 1).

[0008] The above-mentioned interlayer filling structure is increasingly being adopted in mobile devices such as mobile phones that are often used outdoors. In addition, due to the increasing demand for visibility in recent years, in vehicle-mounted applications such as navigation devices, a structure is also being studied in which a front panel is arranged on the surface of the image display panel and an interlayer filling is performed between the panels with an adhesive layer or the like.

[0009] However, when such a structure is adopted, there have been reports that the results of a heat durability test (conducted at 95°C for 200 hours, etc.) showed that a significant decrease in transmittance was observed in the central part of the polarizing plate surface. On the other hand, in the case of a single polarizing plate, no significant decrease in transmittance was observed even under the conditions of 95°C and 1000 hours. There have also been reports that, based on these results, a significant decrease in the transmittance of the polarizing plate in a high-temperature environment is a problem unique to the case where an image display device using an interlayer filling structure in which one surface of the polarizing plate is bonded to an image display unit and the other surface is bonded to a transparent component such as a touch panel or a front panel is exposed to a high-temperature environment (Patent Document 2).

[0010] In addition, in the above-mentioned Patent Document 2, the polarizing plate having an interlayer filling structure and significantly reduced transmittance has a Raman spectroscopic measurement at 1100 cm -1 Nearby (from =CC= key) and 1500cm -1 There is a peak near (derived from the -C=C- bond), so it is considered that a polyene structure (-C=C) is formed. n -, which is presumably caused by polyenylation of the polyvinyl alcohol forming the polarizing element due to dehydration (Patent Document 2, paragraph

[0012] ).

[0011] In addition, the inventors conducted Raman spectroscopy on samples subjected to high temperature durability tests using interlayer filling structures and observed that a decrease in transmittance at 1100 cm -1 Near 1500cm -1 The sum of the areas of nearby peaks is increasing.

[0012] Patent Document 2 proposes a method of suppressing a decrease in transmittance by reducing the moisture content per unit area of ​​the polarizing plate to a predetermined amount or less and reducing the saturated water absorption of a transparent protective film adjacent to the polarizing element to a predetermined amount or less as a solution to this problem.

[0013] However, the results of verification tests conducted by the inventors of the present invention have shown that the reduction and suppression effects of the above-mentioned solutions are not necessarily sufficient. In addition, in order to reduce the moisture content of the polarizing plate when making the panel, the polarizing plate and the panel bonded with the polarizing plate need to be heated, which creates a new problem of reducing the productivity of the panel.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent Application Laid-Open No. 11-174417

[0017] Patent Document 2: Japanese Patent Application Publication No. 2014-102353 Summary of the invention

[0018] Problems to be solved by the invention

[0019] In view of the above situation, the subject of the present invention, that is, the subject to be solved by the present invention is to provide a polarizing plate, which, when used in an image display device composed of interlayer filling, has a small decrease in transmittance under high temperature environment and excellent durability, and to provide a method for manufacturing the polarizing plate. In addition, another object of the present invention is to provide a durable image display device with improved display characteristics under high temperature environment.

[0020] Means used to solve problems

[0021] The present inventors have conducted in-depth research and found that in a structure in which a transparent protective film is provided on at least one surface of a polarizing element formed by adsorbing iodine on a polyvinyl alcohol-based resin layer and orienting the iodine, and in an interlayer filling structure in which one surface of the polarizing plate is bonded to an image display unit and the other surface is bonded to a transparent component such as a touch panel or a front panel by making the adhesive layer contain at least one selected from urea, urea derivatives, thiourea and thiourea derivatives (hereinafter urea, urea derivatives, thiourea and thiourea derivatives are also referred to as "urea-based compounds"), the reduction in transmittance under high temperature environment can be suppressed.

[0022] As a result of further research, it was found that by stacking a layer containing at least one urea compound (hereinafter also referred to as "layer containing urea compound") on at least one surface of the above-mentioned polarizing element, even if the layer is a layer other than the adhesive layer, it is the same as the first invention, and has the effect of suppressing the reduction of transmittance in a high temperature environment in the interlayer filling structure.

[0023] It was also found that in a device using an interlayer filling structure, among the urea compounds of the present invention, urea derivatives or thiourea derivatives not only showed excellent performance in suppressing the decrease in transmittance under high temperature environments, but also showed excellent performance in suppressing the decrease in polarization degree (orthogonal light leakage suppression (Japanese: cross leakage suppression)) under high temperature environments.

[0024] The present inventors have completed the present invention based on such newly discovered facts.

[0025] The problems to be solved by the present invention can be solved by the following means.

[0026] (1) A polarizing plate, characterized in that it has:

[0027] A polyvinyl alcohol-based resin polarizing element that absorbs and orients iodine,

[0028] a layer containing a urea compound selected from urea, urea derivatives, thiourea and thiourea derivatives, formed on at least one surface of the polarizing element; and

[0029] Transparent protective film.

[0030] (2) The polarizing plate according to (1), wherein the layer containing the urea compound is an adhesive layer, and the transparent protective film is bonded to the plate via the adhesive layer.

[0031] (3) The polarizing plate according to (2), wherein the adhesive layer further contains a polyvinyl alcohol-based resin.

[0032] (4) The polarizing plate according to (3), wherein the total content of the urea compound contained in the adhesive layer is 1 part by weight or more and 400 parts by weight or less based on 100 parts by weight of the polyvinyl alcohol resin.

[0033] (5) The polarizing plate according to any one of (1) to (4), wherein the urea compound is a urea derivative and / or a thiourea derivative.

[0034] (6) The polarizing plate according to any one of (2) to (5), wherein the adhesive layer has a thickness of 0.01 to 7 μm.

[0035] (7) The polarizing plate according to (1), wherein the layer containing the urea compound is a resin layer other than the adhesive layer.

[0036] (8) The polarizing plate according to any one of (1) to (7), wherein the polarizing plate is used in an image display device having an interlayer filling structure.

[0037] (9) A method for producing a polarizing plate, characterized in that the method comprises the step of laminating a transparent protective film on at least one surface of a polarizing element.

[0038] The manufacturing method comprises:

[0039] A step of forming an adhesive layer on at least one surface of a polarizing element formed of a stretched polyvinyl alcohol-based resin film obtained by absorbing and orienting iodine, using an adhesive composition containing a polyvinyl alcohol-based resin and at least one selected from urea, a urea derivative, thiourea, and a thiourea derivative; and

[0040] A step of laminating a transparent protective film via the adhesive layer simultaneously with or after the step of forming the adhesive layer.

[0041] (10) An image display device, characterized in that it comprises:

[0042] An image display panel in which the polarizing plate according to any one of claims 1 to 9 is bonded to a visible side surface of an image display unit via an adhesive layer, and

[0043] A transparent member bonded to the viewing side polarizing plate surface of the image display panel via an adhesive layer.

[0044] (11) The image display device according to (10), characterized in that the transparent member is a glass plate or a transparent resin plate.

[0045] (12) The image display device described in (10) is characterized in that the transparent member is a touch panel.

[0046] Effects of the Invention

[0047] According to the present invention, a polarizing plate can be provided, which, when used in an image display device composed of an interlayer filling structure, has a small reduction in transmittance under high temperature conditions and excellent high temperature durability, and a method for manufacturing the polarizing plate is provided. In addition, by using the polarizing plate of the present invention, a display device can be provided in which the reduction in transmittance under high temperature conditions is suppressed. DETAILED DESCRIPTION

[0048] In one embodiment of the present invention, in a configuration in which a transparent protective film is provided on at least one surface of a polarizing element in which iodine is adsorbed and oriented on a polyvinyl alcohol-based resin layer, the adhesive layer contains at least one selected from urea, urea derivatives, thiourea and thiourea derivatives.

[0049] Hereinafter, technical elements constituting the present invention will be described. However, elements other than the layer containing a urea compound are common to other embodiments (an embodiment in which the layer containing a urea compound is a layer other than the adhesive layer).

[0050] [Polarizing element]

[0051] As the polarizing element of the present invention, which is formed by adsorbing iodine on a polyvinyl alcohol (hereinafter also referred to as PVA) resin layer and orienting the iodine, a known polarizing element can be used. Such a polarizing element is generally formed by using a PVA resin film, dyeing the PVA resin film with iodine, and uniaxially stretching it.

[0052] As mentioned above, PVA resins are generally obtained by saponifying polyvinyl acetate resins. The saponification degree is about 85 mol% or more, preferably about 90 mol% or more, and more preferably about 99 mol% to 100 mol%. As polyvinyl acetate resins, in addition to polyvinyl acetate as a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith, such as ethylene-vinyl acetate copolymers, etc., can also be cited. As other monomers that can be copolymerized, for example, unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, etc. can be cited. As the degree of polymerization of PVA resins, it is 1000 to 10000, preferably 1500 to 5000. The PVA resins can be modified, for example, polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc. modified by aldehydes.

[0053] The method for manufacturing the polarizing element is not particularly limited, and a typical method is a method of producing the polarizing element by feeding out a polyvinyl alcohol-based resin film that has been pre-wound into a roll shape and then stretching, dyeing, cross-linking, etc., or a method comprising a step of preparing a laminate of a polyvinyl alcohol-based resin and a stretching resin substrate and stretching the laminate. Any of these methods can be used in the present invention.

[0054] Methods for producing these polarizing elements are described in paragraphs

[0109] to

[0128] of Japanese Patent Application Laid-Open No. 2014-48497, and these methods can be used in the present invention. The thickness of the polarizing element of the present invention is preferably 3 to 35 μm, more preferably 4 to 30 μm, and even more preferably 5 to 25 μm.

[0055] [Layer containing urea compound]

[0056] The polarizing plate of the present invention has a layer containing a urea compound formed on at least one surface of a polyvinyl alcohol-based resin polarizing element formed by absorbing and orienting iodine, and contains at least one selected from urea, urea derivatives, thiourea and thiourea derivatives.

[0057] In the present invention, the layer containing a urea compound does not need to be an adhesive layer, but from the viewpoint of productivity, it is preferred that the adhesive layer contains a urea compound. The adhesive layer is formed of the following adhesive.

[0058] In addition, the structure where the layer containing a urea compound is other than an adhesive layer will be described later.

[0059] [Adhesive]

[0060] Any appropriate adhesive can be used as the adhesive for bonding the protective film to the polarizing element. Specifically, as the adhesive, a water-based adhesive, a solvent-based adhesive, an active energy ray-curable adhesive, etc. can be used, but a water-based adhesive is preferred.

[0061] When the adhesive layer is a layer containing a urea compound, the adhesive contains at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives.

[0062] The thickness of the adhesive during coating can be set to any appropriate value. For example, it can be set in such a way that an adhesive layer having a desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm to 7 μm, more preferably 0.01 μm to 5 μm, further preferably 0.01 μm to 2 μm, and most preferably 0.01 μm to 1 μm.

[0063] (Water-based adhesive)

[0064] In addition, as the above-mentioned water-based adhesive, any appropriate water-based adhesive can be used. Among them, it is preferred to use a water-based adhesive containing a PVA-based resin (PVA-based adhesive). The average degree of polymerization of the PVA-based resin contained in the water-based adhesive is preferably about 100 to 5500, and more preferably 1000 to 4500 from the aspect of adhesion. The average degree of saponification is preferably about 85 mol% to 100 mol%, and more preferably 90 mol% to 100 mol%, from the aspect of adhesion.

[0065] As the PVA resin contained in the above-mentioned water-based adhesive, a resin containing acetoacetyl groups is preferred, because the PVA resin layer has excellent adhesion to the protective film and excellent durability. The PVA resin containing acetoacetyl groups can be obtained, for example, by reacting the PVA resin with diketene using any method. The acetoacetyl modification degree of the PVA resin containing acetoacetyl groups is typically 0.1 mol% or more, preferably about 0.1 mol% to 20 mol%.

[0066] The resin concentration of the water-based adhesive is preferably 0.1% by weight to 15% by weight, and more preferably 0.5% by weight to 10% by weight.

[0067] (crosslinking agent, solvent)

[0068] The water-soluble PVA-based adhesive that can be preferably used in the present invention can also contain a crosslinking agent as required in addition to the above-mentioned PVA-based resin and urea-based compound. As the crosslinking agent, a known crosslinking agent can be used. For example, water-soluble epoxy compounds, dialdehydes, isocyanates, etc. can be cited.

[0069] When the PVA-based resin is an acetoacetyl group-containing PVA-based resin, the crosslinking agent is preferably any of glyoxal, glyoxylate, and methylolmelamine, more preferably any of glyoxal and glyoxylate, and particularly preferably glyoxal.

[0070] The water-soluble PVA-based adhesive of the present invention may contain an organic solvent. In this case, alcohols are preferred from the viewpoint of miscibility with water, and methanol or ethanol is more preferred among alcohols.

[0071] In the present invention, some urea derivatives have low solubility in water but sufficient solubility in alcohol. In this case, the following operation is also one of the preferred methods, that is, after dissolving in alcohol to prepare an alcohol solution of the urea derivative, the alcohol solution of the urea derivative is added to the PVA aqueous solution to prepare the adhesive.

[0072] (Active energy ray-curable adhesive)

[0073] As the above-mentioned active energy ray-curable adhesive, any appropriate adhesive can be used as long as it is an adhesive that can be cured by irradiation with active energy rays. As active energy ray-curable adhesives, for example, ultraviolet curable adhesives, electron beam curable adhesives, etc. can be cited. As specific examples of the curing type of active energy ray-curable adhesives, free radical curing types, cation curing types, anion curing types, and combinations thereof (for example, a mixture of free radical curing types and cation curing types) can be cited.

[0074] Examples of the active energy ray-curable adhesive include an adhesive containing, as a curing component, a compound (eg, a monomer and / or an oligomer) having a radical polymerizable group such as a (meth)acrylate group or a (meth)acrylamide group.

[0075] Specific examples of the active energy ray-curable adhesive and the curing method thereof are described in, for example, Japanese Patent Application Laid-Open No. 2012-144690.

[0076] [Urea compounds]

[0077] In the present invention, the adhesive layer contains at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives.

[0078] As a method for making the adhesive layer contain a urea compound, it is preferable to make the above-mentioned adhesive contain a urea compound. It should be noted that in the process of forming the adhesive layer from the adhesive through a drying step, etc., a part of the urea compound may move from the adhesive layer to the polarizing element, etc.

[0079] Urea compounds include water-soluble compounds and poorly soluble compounds, and any urea compound can be used in the present invention. When a poorly soluble urea compound is used in a water-soluble adhesive, it is preferable to design a dispersion method so that turbidity does not increase after forming the adhesive layer.

[0080] When the adhesive is a water-based adhesive containing a PVA resin, the amount of the urea compound added is preferably 0.1 to 400 parts by weight, more preferably 1 to 200 parts by weight, and even more preferably 3 to 100 parts by weight, based on 100 parts by weight of the PVA resin.

[0081] (Urea or urea derivatives)

[0082] In the present invention, the urea derivative refers to a compound having a molecular structure in which a part of urea is substituted by a substituent. The urea derivative is preferably a compound in which at least one of the four hydrogen atoms in the urea molecule is substituted by a substituent.

[0083] In this case, the substituent is not particularly limited, but is preferably a substituent containing a carbon atom, a hydrogen atom, and an oxygen atom.

[0084] Specific examples of urea derivatives include, for monosubstituted urea, methyl urea, ethyl urea, propyl urea, butyl urea, isobutyl urea, N-octadecyl urea, 2-hydroxyethyl urea, hydroxy urea, acetyl urea, allyl urea, 2-propynyl urea, cyclohexyl urea, phenyl urea, 3-hydroxyphenyl urea, (4-methoxyphenyl) urea, benzyl urea, benzoyl urea, o-tolyl urea, and p-tolyl urea.

[0085] Examples of disubstituted ureas include 1,1-dimethylurea, 1,3-dimethylurea, 1,1-diethylurea, 1,3-diethylurea, 1,3-bis(hydroxymethyl)urea, 1,3-tert-butylurea, 1,3-dicyclohexylurea, 1,3-diphenylurea, 1,3-bis(4-methoxyphenyl)urea, 1-acetyl-3-methylurea, 2-imidazolidinone (ethylene urea), and tetrahydro-2-pyrimidinone (propylene urea).

[0086] Examples of the tetrasubstituted urea include tetramethylurea, 1,1,3,3-tetraethylurea, 1,1,3,3-tetrabutylurea, 1,3-dimethoxy-1,3-dimethylurea, 1,3-dimethyl-2-imidazolidinone, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone.

[0087] (Thiourea or thiourea derivatives)

[0088] In the present invention, the thiourea derivative refers to a compound having a molecular structure in which a part of thiourea is substituted by a substituent. The thiourea derivative is preferably a compound in which at least one of the four hydrogen atoms in the thiourea molecule is substituted by a substituent.

[0089] In this case, the substituent is not particularly limited, but is preferably a substituent containing a carbon atom, a hydrogen atom, and an oxygen atom.

[0090] Specific examples of thiourea derivatives include, for monosubstituted thiourea, N-methylthiourea, ethylthiourea, propylthiourea, isopropylthiourea, 1-butylthiourea, cyclohexylthiourea, N-acetylthiourea, N-allylthiourea, (2-methoxyethyl)thiourea, N-phenylthiourea, (4-methoxyphenyl)thiourea, N-(2-methoxyphenyl)thiourea, N-(1-naphthyl)thiourea, (2-pyridyl)thiourea, o-tolylthiourea, and p-tolylthiourea.

[0091] Examples of the disubstituted thiourea include 1,1-dimethylthiourea, 1,3-dimethylthiourea, 1,1-diethylthiourea, 1,3-diethylthiourea, 1,3-dibutylthiourea, 1,3-diisopropylthiourea, 1,3-dicyclohexylthiourea, N,N-diphenylthiourea, N,N'-diphenylthiourea, 1,3-di(o-tolyl)thiourea, 1,3-di(p-tolyl)thiourea, 1-benzyl-3-phenylthiourea, 1-methyl-3-phenylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea and ethylenethiourea.

[0092] Examples of trisubstituted thiourea include trimethylthiourea, and examples of tetrasubstituted thiourea include tetramethylthiourea and 1,1,3,3-tetraethylthiourea.

[0093] Among the above compounds, urea derivatives or thiourea derivatives are preferred, and urea derivatives are more preferred, from the viewpoint of less reduction in transmittance under high temperature environment and less reduction in polarization degree when used in an image display device composed of interlayer filling. Among urea derivatives, monosubstituted urea or disubstituted urea is preferred, and monosubstituted urea is more preferred. Disubstituted urea includes 1,1-substituted urea and 1,3-substituted urea, and 1,3-substituted urea is more preferred.

[0094] [Transparent protective film]

[0095] The transparent protective film used in the present invention (hereinafter also referred to as "protective film") is bonded to at least one side of the polarizing element via the adhesive layer containing the urea compound of the present invention. The transparent protective film is bonded to one side or both sides of the polarizing element, but is more preferably bonded to both sides.

[0096] In addition, in the structure in which protective films are bonded to both sides of the polarizing element via adhesive layers, only one side of the adhesive layers on both sides of the polarizing element may be the adhesive layer containing the urea compound of the present invention, but it is more preferred that both sides of the adhesive layers are the adhesive layers containing the urea compound of the present invention.

[0097] In recent years, in response to the demand for thinner polarizing plates, polarizing plates having a protective film only on one side of a polarizing element have been developed. In this configuration, it is also preferred that the protective film is laminated via the adhesive layer containing the urea compound of the present invention.

[0098] As a method for producing a polarizing plate having a protective film only on one side of a polarizing element, one can consider first producing a polarizing plate having protective films bonded to both sides via adhesive layers, and then peeling off the protective film on one side. When using this production method, it does not matter which adhesive layer is the adhesive layer of the present invention, but it is more preferred to use the adhesive layer containing the urea compound of the present invention on both sides of the polarizing element.

[0099] When the adhesive layer containing the urea compound of the present invention is used only on one side of the polarizing element, it is preferred that the adhesive layer on the film side not to be peeled is the adhesive layer containing the urea compound of the present invention.

[0100] The protective film may have other optical functions at the same time, and may have a laminated structure in which other layers are laminated.

[0101] From the viewpoint of optical properties, the protective film is preferably thin, but if it is too thin, the strength decreases and the processability deteriorates. The appropriate film thickness is 5 to 100 μm, preferably 10 to 80 μm, and more preferably 15 to 70 μm.

[0102] As the protective film, films such as cellulose acylate resin films, films made of polycarbonate resins, films made of cycloolefin resins such as norbornene, (meth)acrylic polymer films, and polyester resin films such as polyethylene terephthalate can be used.

[0103] In the case of a structure having protective films on both sides of the polarizing element, when bonding using a water-based adhesive such as a PVA-based adhesive, from the perspective of moisture permeability, it is preferred that the protective film on at least one side is either a cellulose acylate film or a (meth) acrylic polymer film, among which a cellulose acylate film is preferred.

[0104] At least one of the protective films may have a phase difference function for the purpose of viewing angle compensation or the like. In this case, the film itself may have the phase difference function, may have a phase difference layer separately, or may be a combination of both.

[0105] In addition, although the structure in which the film having a phase difference function is directly bonded to the polarizing element via an adhesive is described, a structure in which the film is bonded via a pressure-sensitive adhesive or an adhesive via another protective film bonded to the polarizing element may be adopted.

[0106] [Configuration of Image Display Device]

[0107] The polarizing plate of the present invention, i.e., a polarizing plate having a transparent protective film bonded to at least one side of a polarizing element via an adhesive layer containing a urea-based compound, is used in various image display devices such as liquid crystal display devices and organic EL display devices. In particular, the polarizing plate of the present invention can be suitably used in an image display device having an interlayer filling structure in which a transparent member such as a front panel and a touch panel is arranged on the visible side of the image display device, and the image display panel and the transparent member are bonded using an adhesive layer or the like.

[0108] (Image display unit)

[0109] As the image display unit, a liquid crystal unit and an organic EL unit can be cited. As the liquid crystal unit, any of a reflective liquid crystal unit using external light, a transmissive liquid crystal unit using light from a light source such as a backlight, and a semi-transmissive and semi-reflective liquid crystal unit using both light from the outside and light from the light source can be used. In the case where the liquid crystal unit is a liquid crystal unit using light from a light source, in the image display device (liquid crystal display device), a polarizing plate is also configured on the side opposite to the visible side of the image display unit (liquid crystal unit), and a light source is also configured. The polarizing plate on the light source side is preferably bonded to the liquid crystal unit via a suitable adhesive layer.

[0110] As a driving method of the liquid crystal cell, for example, any type of mode such as VA mode, IPS mode, TN mode, STN mode, bend alignment (π mode) can be used.

[0111] As the organic EL unit, an organic EL unit in which a transparent electrode, an organic light-emitting layer and a metal electrode are sequentially stacked on a transparent substrate to form a light-emitting body (organic electroluminescent light-emitting body) can be suitably used. The organic light-emitting layer is a laminate of various organic thin films, for example, a laminate of a hole injection layer containing a triphenylamine derivative or the like and a light-emitting layer containing a fluorescent organic solid such as anthracene, a laminate of these light-emitting layers and an electron injection layer containing a perylene derivative or the like, or a laminate of a hole injection layer, a light-emitting layer, and an electron injection layer can be used.

[0112] (Attachment of image display unit and polarizing plate)

[0113] In laminating the image display unit and the polarizing plate, an adhesive layer (adhesive sheet) can be appropriately used. Among them, from the viewpoint of operability, etc., it is preferred to laminate the polarizing plate with an adhesive layer having an adhesive layer attached to one surface of the polarizing plate and the image display unit. The adhesive layer can be attached to the polarizing plate in an appropriate manner. As an example, for example, a method of preparing an adhesive solution in which about 10 to 40 weight % of a base polymer or a combination thereof is dissolved or dispersed in a solvent containing a single substance or a mixture of appropriate solvents such as toluene and ethyl acetate, and directly attaching it to the polarizing plate by an appropriate development method such as a casting method and a coating method; or a method of forming an adhesive layer on a spacer as described above and then transferring it to the polarizing plate, etc.

[0114] (Adhesive layer)

[0115] The adhesive layer is described in paragraphs

[0103] to

[0143] of JP-A-2018-025765, and these adhesives can be used in the present invention.

[0116] (Transparent front part)

[0117] As the front transparent member disposed on the visible side of the image display unit, a front panel (window layer), a touch panel, etc. can be cited. As the front panel, a transparent plate with appropriate mechanical strength and thickness can be used. As such a transparent plate, for example, a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate, etc. can be used. Functional layers such as an anti-reflection layer can also be stacked on the visible side of the transparent plate. In addition, when the transparent plate is a transparent resin plate, a hard coating layer can be stacked to improve physical strength, and a low moisture permeability layer can be stacked to reduce moisture permeability.

[0118] As the touch panel, various touch panels such as resistive film type, electrostatic capacitance type, optical type, ultrasonic type, etc., glass plates with touch sensor functions, transparent resin plates, etc. can be used. In the case of using an electrostatic capacitance type touch panel as the front transparent member, it is preferred to set a front panel formed of glass or a transparent resin plate on the visible side relative to the touch panel.

[0119] (Attachment of polarizing plate to front transparent member)

[0120] In laminating the polarizing plate to the front transparent member, an adhesive or a UV curable adhesive can be used appropriately. When an adhesive is used, the adhesive can be attached in an appropriate manner. As a specific attachment method, for example, the attachment method of the adhesive layer used in laminating the aforementioned image display unit to the polarizing plate can be cited.

[0121] When a UV curing adhesive is used, in order to prevent the adhesive solution before curing from spreading, the following method can be appropriately used, that is, a dam material is provided in a manner surrounding the peripheral portion on the image display panel, a front transparent member is placed on the dam material, and the adhesive solution is injected. After the adhesive solution is injected, alignment and degassing are performed as needed, and then UV light is irradiated for curing.

[0122] Next, an embodiment of the present invention in which a layer containing a urea-based compound other than an adhesive layer containing at least one urea-based compound is provided on at least one surface of a polarizing element will be described.

[0123] As described above, the technical elements constituting the present invention such as the [polarizing element] other than the [urea compound-containing layer] are the same as those in the embodiment in which the urea compound-containing layer is an adhesive layer.

[0124] [Layer containing urea compound]

[0125] In this aspect of the present invention, the polarizing plate has a layer (other than the adhesive layer) containing a urea compound and containing at least one selected from urea, urea derivatives, thiourea and thiourea derivatives formed on at least one surface of a polyvinyl alcohol-based resin polarizing element formed by absorbing and orienting iodine.

[0126] The layer containing a urea compound preferably has at least one urea compound and a binder. Examples of the binder include polymer binders, thermosetting binders, and active energy ray-curable binders, and any of these binders can be preferably used in the present invention.

[0127] The thickness of the layer containing the urea compound is preferably 0.1 to 20 μm, more preferably 0.5 to 15 μm, and further preferably 1 to 10 μm.

[0128] The layer containing the urea compound may be directly laminated on the polarizing element or may be laminated via another layer. However, it is preferably laminated directly on the polarizing element from the viewpoint of easily suppressing a decrease in transmittance under a high temperature environment.

[0129] In order to improve the physical strength of the polarizing plate, the polarizing plate of this embodiment preferably has a transparent protective film on at least one surface of the polarizing element via an adhesive layer. In this case, the adhesive layer may or may not contain a urea compound, but it is more preferable to contain the urea compound.

[0130] As described in the description of the protective film in other aspects, in recent years, in response to the demand for thinner polarizing plates, polarizing plates having a protective film only on one side of a polarizing element (hereinafter also referred to as "polarizing plates with a protective film on one side") have been developed.

[0131] In such a structure, attempts have been made to laminate a cured layer on the surface of the polarizing element that does not have a protective film in order to improve physical strength, etc. (e.g., Japanese Patent Publication No. 2011-221185)

[0132] In the present invention, a method in which such a cured layer contains a urea compound is also one of the preferred methods. Usually, such a cured layer is formed from a curable composition containing an organic solvent, but paragraphs

[0020] to

[0042] of Japanese Patent Publication No. 2017-075986 describe a method for forming such a cured layer from an aqueous solution of an active energy ray-curable polymer composition. Since urea compounds are mostly water-soluble, it is also one of the preferred methods of the present invention to contain a water-soluble urea compound in such a composition and form a layer containing a urea compound.

[0133] Next, another method of polarizing plate is described, which has a polarizing element produced by coating a solution containing a urea compound on at least one side of the polarizing element and drying it. This method is used for interlayer filling polarizing plates, and its polarizing element has the following characteristics, that is, even when exposed to a high temperature environment for a long time, the decrease in monomer transmittance can be suppressed. After coating at least one side of a polarizing element formed by a stretched polyvinyl alcohol-based resin film obtained by adsorbing iodine and orienting iodine, a solution containing at least one selected from urea, urea derivatives, thiourea and thiourea derivatives is dried, the polarizing element can be produced.

[0134] (Urea compound solution)

[0135] The solvent of the solution containing the urea compound of the present invention is preferably water, an organic solvent or a mixture thereof, more preferably water or a mixed solvent of water and alcohol. In the case of a mixed solvent of water and alcohol, the alcohol is preferably methanol or ethanol.

[0136] As the urea compound, the above-mentioned urea compounds can be preferably used. However, the urea compound is preferably water-soluble from the viewpoint that the urea compound is less likely to precipitate on the surface of the polarizing element after drying.

[0137] Example

[0138] Hereinafter, the present invention will be specifically described based on the examples. The materials, reagents, amounts and ratios thereof, operations, etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the present invention is not limited or restricted by the following examples.

[0139] (Production of Polarizing Element 1)

[0140] A 40 μm thick PVA film having an average degree of polymerization of 2400 and a saponification degree of 99.9 mol% was immersed in warm water at 25°C for 120 seconds to swell. Then, the film was immersed in an aqueous solution of iodine / potassium iodide (weight ratio = 2 / 3) with a concentration of 0.6 wt%, and the PVA film was dyed while being stretched to 2.1 times. Thereafter, the film was stretched in an acid bath containing boric acid and potassium iodide at 60°C, washed with water, and dried to produce a polarizing element 1 having a film thickness of 15 μm.

[0141] (Preparation of PVA solution for adhesive)

[0142] 50 g of a modified PVA-based resin containing an acetoacetyl group (Gohsenx Z-410 manufactured by Mitsubishi Chemical Corporation) was dissolved in 950 g of pure water, and the mixture was heated at 90° C. for 2 hours and then cooled to room temperature to obtain a PVA solution for an adhesive.

[0143] (Preparation of urea compound solution)

[0144] 10 g of urea was added to 90 g of pure water to obtain a 10 wt% urea aqueous solution (solution 1). Similarly, according to Table 1, urea was replaced with the urea compounds described in Table 1 and the solvent was replaced from pure water to methanol as needed to prepare solutions 2 to 9.

[0145] [Table 1]

[0146] Urea (derivatives) Addition amount Solvents Solvent amount Solution 1 Urea 10g Pure water 90g Solution 2 Methyl urea 10g Pure water 90g Solution 3 Ethyl urea 10g Pure water 90g Solution 4 1,3-Dimethylurea 10g Pure water 90g Solution 5 Tetramethylurea 10g Pure water 90g Solution 6 Phenylurea 5g Methanol 95g Solution 7 Thiourea 10g Pure water 90g Solution 8 Methylthiourea 10g Pure water 90g Solution 9 Tetrahydro-2-pyrimidinone 8g Pure water 92g

[0147] Urea, methylurea, ethylurea, 1,3-dimethylurea, tetramethylurea, phenylurea, thiourea, methylthiourea, and tetrahydro-2-pyrimidinone used above were all reagents produced by Tokyo Chemical Industry Co., Ltd.

[0148] (Preparation of Adhesive 1 for Polarizing Plates)

[0149] The PVA solution for adhesive prepared above, urea solution, pure water, and methanol were mixed so that the PVA concentration was 3.0%, the methanol concentration was 20%, and the urea concentration was 0.3%, thereby obtaining Adhesive 1 for polarizing plates.

[0150] (Preparation of Adhesives 2 to 14 for Polarizing Plates)

[0151] Similarly, the adhesive PVA solution, the urea compound solution listed in Table 1, pure water and methanol were mixed so that the PVA concentration was 3.0%, the methanol concentration was 20% and the urea compound concentration was the concentration listed in Table 2 to obtain polarizing plate adhesives 2 to 14.

[0152] It should be noted that the polarizing plate adhesive 12 uses two types of urea compounds, methyl urea and 1,3-dimethyl urea, in combination, while the polarizing plate adhesive 14 does not contain a urea compound.

[0153] [Table 2]

[0154]

[0155] (Saponification of Cellulose Acylate Film)

[0156] A commercially available cellulose acylate film TD40 (manufactured by Fujifilm Corporation: film thickness 40 μm) was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) maintained at 55°C for 2 minutes, then washed with water, and then immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25°C for 30 seconds, and then passed through a water bath under running water for 30 seconds to neutralize the film. Thereafter, water removal using an air knife was repeated three times, and after the water was removed, the film was retained in a drying zone at 70°C for 15 seconds and dried, thereby producing a saponified film.

[0157] (Production of Polarizing Plate 1)

[0158] On both sides of the polarizing element 1, the polarizing plate adhesive 1 is applied, and the thickness of the adhesive layer after drying is adjusted to 100 nm on both sides. The saponified cellulose acylate film prepared above is laminated using a roll laminator and then dried at 60°C for 10 minutes to obtain a polarizing plate 1 with cellulose acylate films on both sides.

[0159] (Production of Polarizing Plates 2 to 14)

[0160] Polarizing plates 2 to 14 were produced in the same manner as in the polarizing plate 1 except that the polarizing plate adhesive 1 was replaced with the polarizing plate adhesives 2 to 14 .

[0161] (Production of Laminated Body 1)

[0162] With reference to the example of Japanese Patent Publication No. 2018-025765, an acrylic adhesive (manufacturer: LINTEC, model: #7) was applied to both sides of the polarizing plate 1 prepared above, thereby preparing an optical laminate 1 having an adhesive layer with a thickness of 25 μm on both sides.

[0163] (Production of Laminated Bodies 2 to 14)

[0164] Optical layered bodies 2 to 14 were produced in the same manner as in the optical layered body 1 except that the polarizing plate 1 was replaced with the polarizing plates 2 to 14 .

[0165] (Production of Laminated Body 15)

[0166] An optical laminate 15 was produced in the same manner as the optical laminate 14 except that the pressure-sensitive adhesive layer was laminated only on one surface of the optical laminate 14 .

[0167] (Evaluation of Laminated Body)

[0168] The laminate produced above was evaluated with reference to the examples of Japanese Patent Publication No. 2014-102353 and Japanese Patent Publication No. 2018-025765. It should be noted that the high temperature durability test was performed at 95°C and 105°C, and the high temperature durability test was performed at 95°C until 1000 hours. Except for Comparative Example 1 using the polarizing plate adhesive 14 without adding a urea compound, no decrease in transmittance was observed. Table 3 shows only the results of the high temperature durability test at 105°C.

[0169] In the test results of Comparative Example 1, the coloration at 105° C.×100 hours is substantially the same as the result at 95° C.×1000 hours.

[0170] [Evaluation of single body transmittance after high temperature durability test (105°C)]

[0171] The optical laminates 1 to 14 prepared above were cut into a size of 50 mm × 100 mm, and the surfaces of the first adhesive layer and the second adhesive layer were bonded to alkali-free glass (trade name "EAGLE XG", manufactured by CORNING), thereby preparing evaluation samples. In addition, the optical laminate 15 was cut into a size of 50 mm × 100 mm, and the surface of the first adhesive layer was bonded to alkali-free glass (trade name "EAGLE XG", manufactured by CORNING), thereby preparing evaluation samples. It should be noted that when preparing these samples, no heating treatment for adjusting the moisture content was performed before bonding the glass plate.

[0172] The evaluation sample was subjected to a temperature of 50°C and a pressure of 5 kgf / cm 2 (490.3 kPa) After 1 hour of autoclave treatment, place in an environment of temperature 23°C and relative humidity 55% for 24 hours. Afterwards, measure the transmittance (initial value), store in a heated environment of temperature 105°C, and measure the transmittance every 50 hours until 100 to 200 hours. Based on the time when the transmittance decreases by more than 5% relative to the initial value, the following criteria are used for evaluation. The results are shown in Table 3.

[0173] In addition, since the evaluation sample including the optical layered body 15 has a structure in which the alkali-free glass is laminated only on one surface, the transmittance does not decrease, and the evaluation result is A.

[0174] Samples with a transmittance drop of 5% or less after 200 hours: A

[0175] Samples whose transmittance drops by more than 5% after 150 to 200 hours: B

[0176] Samples whose transmittance drops by more than 5% under the condition of 100 to 150 hours: C

[0177] Samples with a transmittance drop of 5% or more after 100 hours: D

[0178] [Evaluation of cross light leakage after high temperature durability test]

[0179] The optical laminate 15 was cut into a size of 30 mm×30 mm, and the surface of the first pressure-sensitive adhesive layer was bonded to an alkali-free glass (trade name “EAGLE XG”, manufactured by CORNING CORPORATION) to prepare a sample 20 for orthogonal evaluation.

[0180] After the single transmittance evaluation sample after high temperature durability was evaluated after 100 hours, light leakage in a crossed Nicol prism state (hereinafter also referred to as “crossed light leakage”) was visually evaluated in the optical layered body and sample 20 according to the following criteria.

[0181] Samples where no orthogonal light leakage is observed: ◎

[0182] Samples where almost no orthogonal light leakage is observed: ○

[0183] Samples with slight orthogonal light leakage: △

[0184] Samples where orthogonal light leakage is clearly observed: ×

[0185] [Table 3]

[0186]

[0187] The addition amount of the urea-based compound in Table 3 is described.

[0188] As described above, the amount of the urea compound added to the adhesive is preferably 0.1 to 400 parts by weight, more preferably 1 to 200 parts by weight, and even more preferably 3 to 100 parts by weight, based on 100 parts by weight of PVA.

[0189] In this embodiment, the PVA concentration is 3.0%.

[0190] In the present invention, any urea compound shows a tendency that the more the added amount thereof, the smaller the change in single transmittance after the high temperature durability test. On the contrary, the smaller the added amount thereof, the smaller the orthogonal light leakage after the high temperature durability test.

[0191] All the urea compounds described in the examples showed an effect that the change in single transmittance after the high-temperature durability test was B or more and the cross light leakage was △ or more, and had excellent effects in both performances.

[0192] However, for the amount of the above-mentioned compounds, the addition amount range that shows the preferred performance, that is, the single body transmittance change is greater than B and the orthogonal light leakage is greater than △, is strictly different for each compound. However, the addition amount of any compound has an appropriate range within the preferred addition amount range.

[0193] The addition amounts recorded in Table 3 show the values ​​of the minimum addition amounts for the single body transmittance to reach the evaluation A in each urea-based compound. In addition, for urea and thiourea, the addition amount is gradually reduced from the minimum addition amount to reach the evaluation A, and the value of the addition amount is also shown at which the cross light leakage changes from △ to ○ (the single body transmittance changes to B at this time). In addition, for methyl urea, the addition amount is gradually reduced from the minimum addition amount to reach the evaluation A, and the result of the addition amount is also shown at which the cross light leakage changes from ○ to ◎ (the single body transmittance changes to B at this time).

[0194] From the results shown in Table 3, the following conclusions can be drawn.

[0195] 1. When the polarizing plate of the present invention using an adhesive containing a urea compound is used in an image display device having an interlayer filling structure, a decrease in single-body transmittance can be suppressed even when the polarizing plate is exposed to a high-temperature environment for a long period of time.

[0196] 2. Compared with polarizing plates using urea or thiourea, polarizing plates using urea derivatives or thiourea derivatives are particularly excellent in that they do not have a decrease in single-unit transmittance and do not have cross light leakage.

[0197] 3. A polarizing plate using an adhesive containing two urea compounds can suppress a decrease in single-body transmittance even when the polarizing plate is exposed to a high-temperature environment for a long period of time, which is also one of the preferred aspects of the present invention.

[0198] Other embodiments are described below, but these embodiments are not limited or restricted by the following examples.

[0199] With respect to the composition of the curable layer forming composition BLC-1 described in paragraphs

[0075] to

[0076] of Japanese Patent Publication No. 2017-075986, methyl urea was added so that the solid content concentration of methyl urea was 1% by weight, and pure water was added so that the overall solid content concentration was 26% by weight. After mixing, ultrasonic waves were irradiated, and then passed through a filter with a pore size of 5 μm to prepare a curable composition (UBLC-1) containing a urea compound.

[0200] With reference to the polarizing plate 1 described in paragraphs

[0070] to

[0080] of Japanese Patent Application Laid-Open No. 2017-075986, a single-sided protective film-attached polarizing plate (polarizing plate 22) having a cured layer not containing a urea compound was produced.

[0201] A single-sided protective film-attached polarizing plate (polarizing plate 21 ) having a cured layer containing a urea compound was prepared in the same manner except that the curable forming composition (BLC-1) was replaced with the curable forming composition (UBLC-1) for the polarizing plate 22 .

[0202] Optical layered bodies 21 and 22 were obtained in the same manner as in the optical layered body 14 except that the polarizing plate 14 was replaced with the polarizing plate 21 and the polarizing plate 22, respectively. These samples were evaluated in the same manner as in the optical layered body 14, and the obtained results are shown in Table 4.

[0203] In addition, the evaluation of the orthogonal light leakage after high-temperature durability was performed with the transparent protective film surface facing outward.

[0204] [Table 4]

[0205]

[0206] From the results shown in Table 4, the following conclusions can be drawn.

[0207] 1. The polarizing plate of the present invention having a layer containing a urea compound on at least one surface of a polarizing element can suppress a decrease in single-body transmittance even when exposed to a high temperature environment for a long time when used in an image display device having an interlayer filler structure.

[0208] Another example is given, but this example is not limited or restricted to the following example.

[0209] A 0.5% solution of methyl urea was prepared as a coating solution. The 0.5% solution of methyl urea was applied to one side of the polarizing element 1 prepared above using a bar coater so that the wet coating amount was 10 μm, and dried at 60° C. for 5 minutes to obtain a polarizing element 2 .

[0210] As a comparative example, pure water was applied to one side of the polarizing element prepared above using a bar coater so that the wet coating amount was 10 μm, and the mixture was dried at 60° C. for 5 minutes, thereby obtaining a polarizing element 3 .

[0211] Regarding the polarizing plate 14 , the polarizing plates 31 and 32 were obtained in the same manner except that the polarizing element 1 was replaced with the polarizing element 2 and the polarizing element 3 , respectively.

[0212] Optical layered bodies 31 and 32 were obtained in the same manner as in the optical layered body 14 except that the polarizing plate 14 was replaced with the polarizing plate 31 and the polarizing plate 32, respectively. These samples were evaluated in the same manner as in the optical layered body 14, and the obtained results are shown in Table 5.

[0213] [Table 5]

[0214]

[0215] From the results shown in Table 5, the following conclusions can be drawn.

[0216] 1. The polarizing plate of the present invention, which has a polarizing element produced by coating and drying a solution containing a urea compound on at least one surface of the polarizing element, can suppress a decrease in single-body transmittance even when exposed to a high temperature environment for a long time when used in an image display device having an interlayer filling structure.

Claims

1. A polarizing plate, characterized in that: have: A polyvinyl alcohol-based resin polarizing element that absorbs and orients iodine, a urea-based compound-containing layer containing a urea derivative and / or a thiourea derivative, formed on at least one surface of the polarizing element; and Transparent protective film, The urea derivative is selected from methyl urea, ethyl urea, phenyl urea, 1,3-dimethyl urea and tetramethyl urea, and the thiourea derivative is methyl thiourea. The layer containing the urea compound is an adhesive layer, and the transparent protective film is bonded via the adhesive layer. The adhesive layer also contains a polyvinyl alcohol resin. The total content of the urea compound contained in the adhesive layer is greater than 3 parts by weight and less than 100 parts by weight relative to 100 parts by weight of the polyvinyl alcohol resin. The thickness of the adhesive layer is 0.01 μm to 1 μm, and the thickness of the polarizing element is 4 to 30 μm.

2. The polarizing plate according to claim 1, wherein The polarizing plate is used in an image display device having an interlayer filling structure.

3. A method for manufacturing a polarizing plate, characterized in that: A method for producing a polarizing plate having a transparent protective film bonded to at least one surface of a polarizing element. The manufacturing method comprises: A step of forming an adhesive layer on at least one surface of a polarizing element formed of a stretched polyvinyl alcohol-based resin film obtained by absorbing and orienting iodine, using an adhesive composition containing a polyvinyl alcohol-based resin and at least one selected from a urea derivative and a thiourea derivative; and a step of laminating a transparent protective film via the adhesive layer simultaneously with or after the step of forming the adhesive layer, The urea derivative is selected from methyl urea, ethyl urea, phenyl urea, 1,3-dimethyl urea and tetramethyl urea, The thiourea derivative is methylthiourea, The total content of the urea derivative and / or thiourea derivative contained in the adhesive layer is 3 parts by weight or more and 100 parts by weight or less based on 100 parts by weight of the polyvinyl alcohol resin. The thickness of the adhesive layer is 0.01 μm to 1 μm. The thickness of the polarizing element is 4 to 30 μm.

4. An image display device, characterized in that: have: An image display panel in which the polarizing plate according to any one of claims 1 to 2 is bonded to a visible side surface of an image display unit via an adhesive layer, and A transparent member bonded to the viewing side polarizing plate surface of the image display panel via an adhesive layer.

5. The image display device according to claim 4, characterized in that: The transparent member is a glass plate or a transparent resin plate.

6. The image display device according to claim 4, characterized in that The transparent component is a touch panel.

Citation Information

Patent Citations

  • Liquid crystal panel support, electronic equipment having the same and manufacture of the same equipment

    JP1999174417A

  • Adhesive polarization plate and image display device

    JP2011221185A

  • Active energy ray-curing adhesive agent composition, polarization plate, optical film and image display device

    JP2012144690A

  • Polarizing film with adhesive layer and image display device

    JP2014048497A

  • Polarizing plate and image display device, and manufacturing method of those

    JP2014102353A